2007
DOI: 10.1143/jjap.46.1250
|View full text |Cite
|
Sign up to set email alerts
|

Ge-Channel Thin-Film Transistor with Schottky Source/Drain Fabricated by Low-Temperature Processing

Abstract: The state-selective dissociation dynamics for anionic and excited neutral fragments of gaseous SiCl 4 following Cl 2p and Si 2p core-level excitations were characterized by combining measurements of the photoninduced anionic dissociation, x-ray absorption and UV/visible dispersed fluorescence. The transitions of core electrons to high Rydberg states/doubly excited states in the vicinity of both Si 2p and Cl 2p ionization thresholds of gaseous SiCl 4 lead to a remarkably enhanced production of anionic, Si − and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In addition, the obtained mobility in this experiment is almost the same mobility (100–140 cm 2 V −1 s −1 ) as that for poly-Ge channel TFTs reported by Sadoh et al where the maximum process temperature was 500 °C in the SPC of a-Ge films [66, 67]. From these results, we can say that the 2% Sn incorporation into Ge can effectively improve the mobility, especially when low-temperature annealing is used; however, it is desirable to increase the hole mobility further because the mobility is still smaller than that of single-crystalline Si.…”
Section: Crystal Growth and Crystalline Propertiessupporting
confidence: 85%
“…In addition, the obtained mobility in this experiment is almost the same mobility (100–140 cm 2 V −1 s −1 ) as that for poly-Ge channel TFTs reported by Sadoh et al where the maximum process temperature was 500 °C in the SPC of a-Ge films [66, 67]. From these results, we can say that the 2% Sn incorporation into Ge can effectively improve the mobility, especially when low-temperature annealing is used; however, it is desirable to increase the hole mobility further because the mobility is still smaller than that of single-crystalline Si.…”
Section: Crystal Growth and Crystalline Propertiessupporting
confidence: 85%
“…Ge is one of the most attractive materials that meet the above requirements because it has a higher carrier mobility for both electrons and holes 1) and a lower polycrystallization temperature 2) than Si. From this background, many research groups have demonstrated the individual fabrication of p- [3][4][5][6] and n-type 7,8) polycrystalline Ge (poly-Ge) field-effect transistors (FETs) on insulating layers; in addition, poly-Ge CMOS operation has been achieved by Kamata et al 9) These studies are informative in the field of 3D-ICs. However, hightemperature lamp annealing above 840 °C is required for crystallizing an amorphous Ge (a-Ge) layer on SiO 2 ; also, annealing at a temperature as high as 600 °C is necessary for recrystallization and dopant activation after the ion implantation of n-type dopants.…”
Section: Introductionmentioning
confidence: 99%
“…In the TFTs using Ge channel, device has been fabricated with polycrystalline-Ge on a glass substrate. Because the film is polycrystalline, mobility becomes even lower by scattering at grain boundaries [3]. Off current becomes also very large due to carrier generation at the boundaries, resulting in very small on/off current ratio.…”
Section: Introductionmentioning
confidence: 99%